Complete mitochondrial genome sequence of the Rattus norvegicus SILN strain with central nervous system disorder. (3rd May 2016) - Zhang, Yu-Zhen; Lou, Ji-Yu; Zhang, Chang-Meng; Li, Jin-Feng; Yin, Hong-Lei; Wang, Yun-Liang
Abstract: The Rattus norvegicus SILN strain is a common used model for nervous system disorder disease study. We sequenced this R. norvegicus strain SILN mitochondrial genome for the first time (GenBank Accession No. KM114606). Its mitogenome was 16, 311 bp and coding 13 protein-coding genes, 2 ribosomal RNA genes, 22 transfer RNA genes.